Keterampilan Berpikir Kritis dalam Pembelajaran Pendidikan Agama Islam pada Aspek Taksonomi Bloom dan Manifestasi Belajar - Leni Marliani; Nesha Asmilia Gustin; Taufik Rahman (Institut Agama Islam Sumatera Barat, 2024)
This research applies a descriptive qualitative method with a literature study approach to explore critical thinking skills in Islamic Religious Education learning. The main focus of this research is to analyse the relationship between cognitive, affective and psychomotor aspects in improving the quality of learning. Literature review is used as the main method to comprehensively understand the application of critical thinking skills in the educational context. The results show that effective education should include mastery of academic material, development of positive attitudes, as well as practical skills for learners to achieve better competence and contribute significantly in society. The findings provide insights for educators and researchers in improving the quality of education through appropriate approaches. Thus, this research is expected to be a reference in the application of critical thinking skills in learning Islamic Religious Education to support the improvement of the quality of human resources.